2014
DOI: 10.1302/0301-620x.96b8.31587
|View full text |Cite
|
Sign up to set email alerts
|

Mid-to long-term results of revision total hip replacement in patients aged 50 years or younger

Abstract: Revision total hip replacement (THR) for young patients is challenging because of technical complexity and the potential need for subsequent further revisions. We have assessed the survivorship, functional outcome and complications of this procedure in patients aged < 50 years through a large longitudinal series with consistent treatment algorithms. Of 132 consecutive patients (181 hips) who underwent revision THR, 102 patients (151 hips) with a mean age of 43 years (22 to 50) were reviewed at a mean follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
0
28
0
2
Order By: Relevance
“…Survival at 5-year follow-up was lower when compared with the available literature on young patients (Lee et al 2014, Gromov et al 2015, Te Stroet et al 2015. Few papers ana- Table 3.…”
Section: Comparison With Literaturementioning
confidence: 92%
See 2 more Smart Citations
“…Survival at 5-year follow-up was lower when compared with the available literature on young patients (Lee et al 2014, Gromov et al 2015, Te Stroet et al 2015. Few papers ana- Table 3.…”
Section: Comparison With Literaturementioning
confidence: 92%
“…Te Stroet et al (2015) reported a survival rate of 87% after follow-up of 10 years in a single-center study with only 34 revision procedures. Lee et al (2014) reported a survival rate of 63% at 10-year follow-up, whereas survival at 5 years was approximately 88%. Several studies assessed the survival of revision hip arthroplasty in older patients, where reported survival varied between 81% and 83% at 5 years (Jafari et al 2010, Ong et al 2010 and 72% at 10 years (Lie et al 2004).…”
Section: Comparison With Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The increasing number of THAs performed in patients younger than 55 years will inevitably generate a larger number of revision procedures for this specific group of patients. Unfortunately, data on the recent results of revision THA in younger patients are limited, and survivorship data from studies of younger patients are not encouraging [ 1 , 16 , 22 ]. The single long-term survival study reports a disappointing outcome of 63% at 10 years for patients when the endpoint was rerevision for any reason [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, with longer survivorship of artificial hips, young patients become more and more candidates for THA, as other surgical options are limited [4]. For this reason, radiation exposure is increasingly becoming a focus.…”
Section: Introductionmentioning
confidence: 99%